Relationship between hardness and myowater properties in Wooden Breast affected chicken meat: A nuclear magnetic resonance study. (December 2017) - Tasoniero, Giulia; Bertram, Hanne Christine; Young, Jette Feveile; Dalle Zotte, Antonella; Puolanne, Eero
Abstract: The role of myowater-holding on the development of the hardness of Wooden Breast (WB) affected chicken breasts was investigated. Transverse (T2 ) relaxation times and proportions of myowater populations ( T 2B, T 21 and T 22 ) were assessed using low-field nuclear magnetic resonance (NMR) relaxometry and integrated with meat compression measurements. Two muscle conditions (M: Normal (N) vs WB), four sampling locations (L), four sampling times (T) and interactions (M x L and M x T) were considered. Compared to N, WB was harder, the extramyofibrillar myowater population (T22 ) was increased and the relaxation time of the water trapped into the myofibrillar matrix (T21 ) was also increased. A link between the T 21 relaxation time of water trapped into the myofibrillar matrix and hardness was suggested for the WB muscles. During storage, a redistribution of water occurred over time, as revealed by an increasing trend of the T 21 population, but a concomitant texture evolution did not reflect this change. The cranial/superficial part of the breasts exhibited the highest amount of the extramyofibrillar water population ( T 22 ), and the texture of this muscle part was harder than the deep layers. However, the role of myowater on muscle hardness was not fully clarified by this study. Highlights: T 2B and T 21 -relaxation times were longer in Wooden Breast than in Normal muscle. The amount of extramyofibrillar water was higher in Wooden Breast. In normal muscle, as the protein-bound water increased the hardness decreased. In Wooden Breast, as the intramyofibrillar water decreased the hardness increased. Wooden Breast in cranial/superficial area resulted in more extramyofibrillar water.